Semantic Analysis on Deontic Modality of Angkola Language as Politeness Maker - Dalimunte, Muhammad (Advances in Social Sciences Research Journal, 2024)
Social interaction is a necessity for everyone in ethnic groups (microscope) and nations (macro scope). Language as a group identity is very close to cultural values ​​that must be considered by the language users. The object of this study is one of the Ethnic languages ​​in North Sumatra, which is Angkola Language. The aspect discussed in this language is the use of modals in command sentences (deontic modality seen from a semantic perspective). This research used a descriptive method with a qualitative approach. The data of this study are Oral and Written Data of Angkola Language. The research finding shows that there are three values of deontic Modality in Angkola Language: 1) High degree: ulang (don’t /no), musti/musti akkon (must), tarpaksa (has/has to), 2) Median degree: akkon (should), 3) Low degree: tola (may), na tola, inda tola (may not), izin /izitkon (allow), na diizitkon (not allowed), inda bisa/na bisa (not allowed), dipatola/inda dipatola (allowed/not allowed), Akkon (Ought to) and The particle as modality markers: da, ma, mada to create the polite expression.